Repeated cesarean section surgery in women with two or more scars on the uterus - N. M. Yametova; V. B. Tskhay; M. Y. Domracheva (Медицинский вестник Юга России, 2021)
Objective: To monitor the outcome of surgical delivery of pregnant women with two or more uterine scars aft er Cesarean section.Materials and Methods: A retrospective study was performed based on the Krasnoyarsk Regional Clinical Center for Maternal and Child Health. The analysis of birth histories and histories of newborns in pregnant women who delivered by Caesarean section with two or more scars on the uterus within 2020 was carried out. Inclusion criteria: single pregnancy of 22 weeks or more, the presence of two or more scars aft er Cesarean section. Exclusion criteria: pregnancy less than 22 weeks, one scar on the uterus, and a scar on the uterus aft er other operations. Pregnant women with multiple pregnancies.Results: The severity of the adhesive process in the abdominal cavity was noted only in patients with three or more uterine scars. An increase in the duration of the Cesarean section operation of more than 60 minutes was observed in the group with three uterine scars and more (40%). Low risk of injuries to neighboring organs, intestines, ureters, and bladder was observed in groups of patients with both two and three uterine scars. More oft en, intraoperative massive blood loss was noted in the group with three scars on the uterus and more (16.67%). Moderate and severe asphyxia in newborns was registered in the group with three or more uterine scars (16.65%).Conclusion: Th e presence of one and/or two scars on the uterus aft er Cesarean section allowed the authors to classify these pregnant women as a low-risk group. The presence of three or more scars on the uterus aft er Cesarean section classifi ed these pregnant women as a high-risk group.